Factors that influence the lack of breast milk in milk banks: Literature review (Research, Society and Development, 2024)
Objective: to describe the factors that influence the lack of breast milk in human milk banks. Methodology: This is a descriptive integrative literature review. The data was searched through the electronic media Scientific Electronic Library Online (SciELO), Latin American and Caribbean Health Sciences Literature (LILACS), National Library of Medicine (PubMed) which covers the Medical Literature Analysis and Retrieval System Online (MEDLINE) databases and an academic search engine, Google Scholar. Health Sciences Descriptors (DeCS) were used to search the literature, with the following terms being used: "breastfeeding", "human milk bank", "health promotion" and one in English using the term "milk banks". The terms were cross-referenced and used individually in the sampling. The inclusion criteria were to keep articles and theses that were related to the theme addressed, available in the selected databases with full text, free of charge and in Portuguese and English, published between 2015 and 2024. The exclusion criteria were repeated publications, publications in other languages, abstracts, theses, previous notes, monographs, dissertations and incomplete articles and/or articles that did not address the proposed theme. Results: 23 studies were found that addressed the theme and were used in the discussion. Conclusion: Several barriers prevent the donation of human milk to HMBs, but few studies have been carried out on the subject. However, by taking a bibliographic approach to the existing profile of donors, professionals can be better informed in order to influence and thus increase the volume of human milk in HMBs.